Predictive model of sexual infidelity behavior among married persons - Moral-de-la-Rubia, José (Universidad Autónoma de Tamaulipas, 2020)
Marital infidelity is relatively frequent despite its consequences. The aim of the study was to develop a predictive model of sexual infidelity behavior among married persons through the analysis of seven variables related to the infidelity construct. A sample of 790 married persons (53.4 % women and 47.6 % men) was collected in Monterrey, Mexico, using random route sampling. The Relationship Assessment Scale, Sexual Satisfaction Index, Attitude toward Marital Exclusivity Scale, Unfaithful Behavior Scales, Sexual Sensation Seeking Scale, and Marital Aggrandizement Scale were applied. A model with 2 correlated exogenous variables (sexual sensation seeking and marital aggrandizement) and 5 endogenous variables (attitude towards infidelity, marital satisfaction, sexual satisfaction, desire for sexual infidelity, and sexual infidelity behavior) was specified. Six out of 100 participants were dissatisfied with their marriage and 13 with sexual relations with their partner; 20 saw more defects than virtues in their partners. In addition, 83 informed not engaging in sexual infidelity behaviors, 60 indicated total rejection towards own sexual infidelity; 72 showed no desire for sexual infidelity; and 51 reported not seeking sexual sensations. The model showed a large effect on the sexual infidelity behavior, explaining 70.8 % of its variance, and had a close fit: X2(7) = 11.93, P-value = 0.10, RMSEA = 0.03, and SRMR = 0.01. It is concluded that the most critical variable in the model is the desire for sexual infidelity, whose most important determinant was the sexual sensation seeking. The negative correlation between this last variable and marital aggrandizement indicates that these 2 variables can be modulated one to the other. Furthermore, the model highlights aspects of marital and sexual dissatisfaction.